The forgotten Resource: Corporate Governance and Employee Board-Level Representation. The Situation in France, the Netherlands, Sweden and the UK - Lionel Fulton (Hans-Böckler-Stiftung, 2007)
Corporate governance - the way that major businesses are run - has been of in-creasing concern in recent years. Financial scandals in companies like Enron and WorldCom, as well as similar problems in Europe, have resulted in most major countries introducing corporate governance codes. However, these codes need to be seen in relation to long-established national structures of corporate governance, which are often very different - in their forms, in their participants, and even in their purpose. In particular, employee representatives have a clear and important role in some, but no place at all in others.This study looks at governance structures and corporate governance codes in four separate European states: France, the Netherlands, Sweden and the UK. The four represent very different traditions of corporate governance - shareholder value is dominant in the UK, for example, while in the Netherlands companies are to be run in the long-term interest of all those involved. The UK is also the only country of the four where employees are not involved, at least to some degree, at board level.Despite these differences, the study shows that the corporate governance codes that have been introduced in each state are very similar. Indeed, the committees drawing them up, faced with the need to meet the expectations of international investors, have deliberately chosen common solutions. One clear result is that these codes largely neglect the role that employee represen-tatives play at board level. The evidence, presented in the study, is that employee representatives on company boards are overwhelmingly seen as positive. However, in the world of corporate governance codes, they remain a forgotten resource.The study draws together information from four national reports, and, as well as presenting the overall picture, includes executive summaries from each state.
Keywords: 330; Corporate Governance; Mitbestimmung; Vorstand; Frankreich; Niederlande; Schweden; Großbritannien